Oral Care Colostrum Effect on Preterm Infants Fecal Immunoglobulin A Secretory Level - Eko Wahyudi1 , Martono Tri Utomo2 , Risa Etika2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective To evaluate whether oral care colostrum can increase fecal secretory immunoglobulin A levels inpreterm infants.Methods Thirty-eight infants who met the inclusion criteria were randomized. Twenty colostrum oral careinfants and eighteen control control infants. Colostrum oral care by giving as much as 0.1 ml of colostrumon each buccal mucosa for approximately 2 minutes on one side. The procedure is repeated every 4 hoursfor 3 days. Fecal secretory immunoglobulin A levels are taken from the first faecal after birth and 72 hoursafter colostrum administration. Fecal retrieval must first install a urine device so that the urine does not wetthe sample.Result Fecal secretory immunoglobulin A level before treatment in the treatment group were 0.0633 ±0.0037 mg/g feces higher than the control group 0.0166 ± 0.0139 mg/g feces, statistically there were nosignificant differences (p = 0.595). Fecal secretory immunoglobulin A level after treatment in the treatmentgroup amounted to 1,1007 ± 0.2458 mg/g feces higher than the control group 0.6045 ± 0.2358 mg/g faeces,statistically there were no significant differences (p = 0.09 ). Difference in increase in secretory fecalimmunoglobulin A levels after and before treatment in the treatment group 1.0374 ± 0.2575 mg/g feces ishigher than the control group 0.5879 ± 0.2385 mg/g feces, statistically there were no significant differences(p = 0.09).Conclusion Oral care colostrum has been shown to increase secretory immunoglobulin A levels in preterminfants before colostrum oral care, and colostrum oral care has the potential to increase faecal secretoryimmunoglobulin A level than controls in preterm infants.